Automated Threat Detection for Disaster Response Teams Using UAV Platforms. - Schweig, Andrew M. (Tufts Archival Research Center, 2014)
Abstract: I present a sensor system, mountable on a commercially available unmanned aerial vehicle (UAV). The system comprises of real-time video, radiation detection, and vehicle telemetry. I present methods of integrating hardware and software with existing frameworks. The system is intended for use by disaster first response teams to prevent injury or loss of human life during site surveillance.